2009
DOI: 10.1007/bf03182390
|View full text |Cite
|
Sign up to set email alerts
|

The effects of peer education on university students' knowledge of breast self-examination and health beliefs

Abstract: This study was carried out to determine the effects of peer education on breast self-examination (BSE) knowledge and health beliefs. 180 female university students were trained in BSE by the nursing students. Students instructed in groups by their peers showed a much higher degree of BSE knowledge. It was also found that perceived confidence of the students educated both individually and in groups increased afterward. Study results further revealed that the methods used for peer instruction do not affect stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 13 publications
5
39
0
2
Order By: Relevance
“…Mammography, clinical breast examination and BSE are the methods used for screening in the early detection of breast cancer (16,17). According to the literature, BSE is a cheap, simple, safe and effective method and acquiring BSE behaviors and practices will increase the possibility to continue BSE in the future (18). The study was done in order to determine the effects of peer education upon BSE practices and self-esteem among the university students.…”
Section: Discussionmentioning
confidence: 99%
“…Mammography, clinical breast examination and BSE are the methods used for screening in the early detection of breast cancer (16,17). According to the literature, BSE is a cheap, simple, safe and effective method and acquiring BSE behaviors and practices will increase the possibility to continue BSE in the future (18). The study was done in order to determine the effects of peer education upon BSE practices and self-esteem among the university students.…”
Section: Discussionmentioning
confidence: 99%
“…Although BSE is recommended in the early diagnosis of breast cancer, it was shown that BSE was made irregularly or never made in the studies conducted on women of all age groups and students (2,(8)(9)(10)(11)(12)(13)(14). Researches indicate the importance of education in increasing the rate of BSE (10,11,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when it is considered that mammography, which is accepted as the gold standard in the diagnosis of breast cancer, is not used in young women, BSE becomes more important. When the socio-economical facts are also considered especially in developing countries with middle income such as Turkey, BSE is regarded as an indisputable practice (5, 7).Although BSE is recommended in the early diagnosis of breast cancer, it was shown that BSE was made irregularly or never made in the studies conducted on women of all age groups and students (2,(8)(9)(10)(11)(12)(13)(14). Researches indicate the importance of education in increasing the rate of BSE (10,11,(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Breast self-examination (BSE), clinical breast examination and mammography are recommended for detecting breast cancer at an early stage (Altunkan et al, 2008;Secginli 2011;Ersin and Bahar, 2012;Yilmaz et al, 2013). The practice of BSE every month has been reported to be considerably important for early detection of breast cancer particularly among women over 20 years of age (Gursoy Akkaş et al, 2009;Koc and Saglam 2009).…”
Section: Introductionmentioning
confidence: 99%